Gay and lesbian characters’ treatment in Basque contemporary short-story-writing - Satrustegi Andrés, Iñigo (EGAN, 2021)
It is said Basque short-story-writing to be recently increasing as a narrative gender. Likewise, hegemonic sexuality and gender dissents, that is to say, the LGTBI+ community, is more accepted and common in our society. Thus, this research aims at yoking both subjects under examination. We will be analysing a small sample of short-stories written in Basque language form the latest decades, and we will see how are treated homosexual –gays and lesbians– characters in those. Briefly, this paper will analyse sexuality-topics proposed in literary re- searches to see whether they are embodied or not (and how) in contemporary Basque literature.